Relevante Zufallsbefunde und iatrogene Verletzungen: Eine retrospektive Analyse von 1165 Schockraumpatienten = Relevant incidental findings and iatrogenic injuries : A retrospective analysis of 1165 resuscitation room patients - Viergutz, Tim; Terboven, Tom; Henzler, Thomas; Schäfer, D.; Schönberg, Stefan; Janssen, Sonja (Der Anaesthesist, 2018)
Abstract: Whole-body computed tomography (CT) is increasingly being used as the diagnostic modality of choice in patients admitted to the resuscitation room. Beyond findings related to the suspected diagnosis it often additionally reveals incidental findings. The aim of this investigation was the evaluation of these findings in patients admitted via the emergency room after suffering potential major trauma or life-threatening medical conditions. Furthermore, the number of iatrogenic injuries as well as misplaced catheters and endotracheal tubes was investigated. METHODS:All patients admitted from 1 February 2012 to 31 January 2014 via the resuscitation area of the Mannheim University Medical Center, a tertiary care hospital and level 1 trauma center, were included in this study if they had undergone a whole-body CT scan at admission. Data from 1362 patients were collected retrospectively and 197 patients were excluded because of missing data so that the final cohort consisted of 1165 patients (1038 trauma and 127 internal neurological patients). Reports from the whole-body CT scans were screened for incidental findings. These findings were then classified as either clinically relevant or not. Furthermore, the reports were checked for iatrogenic injuries as well as misplaced catheters and endotracheal tubes. RESULTS:A total of 465 incidental findings were reported in 293 patients (25.1%) of the final cohort. In the synopsis of the radiological and clinical findings, 72 were rated as clinically relevant. In one patient two relevant incidental findings were reported and one patient presented with three incidental findings. In total, relevant incidental findings could be detected in 5.8% of the study patients (68/1165). In the discharge letters and/or the radiological report 16.2% of the incidental findings rated as clinically relevant were reported to be previously known, 66.2% were reported to be unknown and 17.6% could not be unequivocally classified as known or unknown due to missing references in the discharge letters. The group of internal neurological patients were clearly older than the trauma patients (61.6 years vs. 45.5 years). The rate of relevant incidental findings in the internal neurological group was more than twice as high as in the trauma group (11.0% vs. 5.2%); however, in the relatively young trauma group 1 in 20 patients showed an incidental finding classified as clinically relevant. In 43 (3.7%) patients a total of 46 iatrogenic injuries or misplaced catheters were reported. The most common finding was a too deeply placed endotracheal tube and five transurethral catheters placed in the emergency room were found to be blocked within the urethra. CONCLUSION:In addition to the main diagnosis, clinically relevant incidental findings were reported in nearly 25% of whole-body CT scans of patients admitted to the resuscitation room. Approximately 6% of patients had incidental findings rated as clinically relevant. In the internal neurological group of patients the rate of incidental findings was doubled compared to the trauma group; however, the latter were significantly younger. Whole-body CT was also useful for diagnosing iatrogenic injuries and misplaced catheters in approximately 4% of the study patients.